Permohonan Pailit terhadap developer perumahan dalam Praktik Peradilan di Indonesia dan Malaysia - Agung Hermansyah; Harul Surya Fernanda; Novaranty Zura Dwiputri (Journal of Law Perspectives Review, 2025)
This article aims to comparatively examine the legal mechanisms for filing bankruptcy petitions against housing developers in Indonesia and Malaysia, with a particular focus on the effectiveness of consumer protection. The research is motivated by the rising number of stalled housing projects and the weakened legal position of consumers, especially in Indonesia following the issuance of Supreme Court Circular Letter (SEMA) No. 3 of 2023, which restricts the use of bankruptcy petitions against property developers. This study employs a normative legal research method with a comparative law approach, analyzing statutory regulations, court decisions, and relevant legal literature from both countries. The findings reveal that Malaysia offers a more consumer-responsive insolvency framework through the implementation of escrow accounts, performance bonds, clear legal segmentation between individual and corporate bankruptcy, and the presence of a dedicated housing regulatory authority. In contrast, Indonesia continues to face legal uncertainty and lacks sufficient consumer protection mechanisms in bankruptcy cases involving developers. The study concludes that Indonesia’s bankruptcy law requires reform to become more adaptive and consumer-oriented. The recommendation includes strengthening bankruptcy regulations, integrating escrow account mechanisms into national law, and establishing an independent housing supervisory body to enhance developer accountability and ensure legal certainty for homebuyers.